Histochemical Study of Levator Veli Palatini Muscle in Patients with Velopharyngeal Incompetence - TAKADA, Satoshi; WADA, Takeshi; HARA, Hisanaga; SATO, Koichi; TACHIMURA, Takashi; OHNO, Tomoya (Journal of Japanese Cleft Palate Association, 1999)
This study was undertaken to investigate the relation b etween histochemical findings of levator veli palatini muscle fiber compositions and fiberscopic findings of velopharygeal movement in patients who underwent operation for cleft palate. Eight of these patients who were candidates for pharyngeal flap surgery for velopharyngeal incompetence were the subjects. Velopharyngeal function for each subject was investigated using nasopharyngeal fiberscope prior to surgery. Specimens of the levator veli palatini muscle were removed at the time of surgery. Specimens were fixed by quick-freezing, and stained with H-E and ATPase histochemistry in cryostat sections. The results were as follows: 1. For two subjects showing adequate timing of velum movement, this was the coronal pattern of velopharygeal movement, and the muscle fibers were arranged in mosaic pattern of type 1,2A and 2B fibers. 2. For four subj ects showing poor velum movement, this was coronal to circular or circular to sagital, and the muscle fibers compositions were variable compared to those of subjects with adequate velopharyngeal movement. 3. For the remaining two subjects sho wing immobile velum, no muscle fiber was observed. It was suggested that histochemical findings correspond to fiberscopic findings of velopharygeal movement.